Development of Gait Rehabilitation System Capable of Assisting Pelvic Movement of Normal Walking - Jung, Chanyul; Jung, Suhun; Chun, Min Ho; Lee, Jong Min; Park, Shinsuk; Kim, Seung-Jong (Okayama Daigaku, 2018)
Gait rehabilitation training with robotic exoskeleton is drawing attention as a method for more advanced gait rehabilitation training. However, most of the rehabilitation robots are mainly focused on locomotion training in the sagittal plane. This study introduces a novel gait rehabilitation system with actuated pelvic motion to generate natural gait motion. The rehabilitation robot developed in this study, COWALK, is a lower-body exoskeleton system with 15 degrees of freedom (DoFs). The COWALK can generate multi-DoF pelvic movement along with leg movements. To produce natural gait patterns, the actuation of pelvic movement is essential. In the COWALK, the pelvic movement mechanism is designed to help hemiplegic patients regain gait balance during gait training. To verify the effectiveness of the developed system, the gait patterns with and without pelvic movement were compared to the normal gait on a treadmill. The experimental results show that the active control of pelvic movement combined with the active control of leg movement can make the gait pattern much more natural.